Pengembangan Flipbook Bahan Ajar IPA Kelas V Terintegrasi Tri- N Untuk Meningkatkan Dimensi Kreatif Peserta Didik - Riza Indah Pramesti; Akbar Al Masjid (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
Currently, teachers are required to design and implement active, creative and innovative learning so that they can encourage students to learn better. One of the subjects in the Merdeka Curriculum is science lessons. With interesting media, students will feel happy and interested in participating in learning. An alternative solution that can be applied to increase the creativity of elementary school students is to develop flipbook learning media by implementing project-based learning that is integrated with the teachings of Ki Hadjar Dewantara, namely the Tri-N teachings which include niteni, niroake and nambahake. The flipbook learning media is designed to be as efficient as possible so that it can foster the creativity dimension of students. With the development of flipbook media, it is hoped that students will be more enthusiastic in learning. Based on the results of the implementation of flipbook-based digital science learning module products in science learning, response data was obtained from fifth grade elementary school students as product users, that the flipbook-based digital science learning module products that have been developed are liked by students and can help increase students' learning motivation in learning, can help them learn the materials studied, and can increase their creative dimensions.